Pengaruh Penambahan Kencur (Kaempferia galanga L.) Terhadap Karakteristik Kimia Dan Sensori Hard Candy Beras Kencur - Lesmana, Yeni; Kartika Pratiwi, I Desak Putu; Ayu Ekawati, I Gusti (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i01.p03, 2022)
This study was aimed to determining the effect of adding galangal on the characteristics of beras kencur hard candy and to get the right amount of galangal to produce the best characteristics beras kencur hard candy.This study used a completely randomized design (CRD), with the addition of galangal treatment which consisted of 5 levels (10%; 20%; 30%, 40%; 50%). The treatment was repeated 3 times to obtain 15 experimental units. The data were analyzed by analysis of variance if the treatment had a significant effect, then followed by the Duncan’s Multiple Range Test (DMRT). The result showed, the addition of galangal in beras kencur had a significant effect on antioxidant activity IC50, flavor and taste (scoring).Addition beras kencur with concentration galangal 50% produced the best characteristic of beras kencur hard candy with criteria: water content 1.79%, ash 0.52%, total of sugar 4.46%, reducing of sugar 3.05%, sucrose 1.35%, and antioxidant activity IC50 9383.62 ppm.Sensory properties obtained are the color, texture, odor, taste, and overall acceptance is slightly liked. As well as the sharp odor and taste of galangal.